New Strait Times, 22 November 2010 - Donald G,McNeil Jr (The New Straits Times Press (M) Bhd, 2010)
If United Nation peacekeepers from Nepal are going to be blame for bringing cholera to Haiti, it's important to remember that the blame game for pandemics eventually involve everyone.